Genomic Characterization of a Novel Gut Symbiont From the Hadal Snailfish - Lian, Chun-Ang; Yan, Guo-Yong; Huang, Jiao-Mei; Danchin, Antoine; Wang, Yong; He, Li-Sheng (Frontiers in Microbiology, 2020)
Hadal trenches are characterized by not only high hydrostatic pressure but also scarcity of nutrients and high diversity of viruses. Snailfishes, as the dominant vertebrates, play an important role in hadal ecology. Although studies have suggested possible reasons for the tolerance of hadal snailfish to high hydrostatic pressure, little is known about the strategies employed by hadal snailfish to cope with low-nutrient and virus-rich conditions. In this study, the gut microbiota of hadal snailfish was investigated. A novel bacterium named “Candidatus Mycoplasma liparidae” was dominant in the guts of three snailfish individuals from both the Mariana and Yap trenches. A draft genome of “Ca. Mycoplasma liparidae” was successfully assembled with 97.8% completeness by hybrid sequencing. A set of genes encoding riboflavin biosynthesis proteins and a clustered regularly interspaced short palindromic repeats (CRISPR) system was present in the genome of “Ca. Mycoplasma liparidae”, which was unusual for Mycoplasma. The functional repertoire of the “Ca. Mycoplasma liparidae” genome is likely set to help the host in riboflavin supplementation and to provide protection against viruses via a super CRISPR system. Remarkably, genes encoding common virulence factors usually exist in Tenericutes pathogens but were lacking in the genome of “Ca. Mycoplasma liparidae”. All of these characteristics supported an essential role of “Ca. Mycoplasma liparidae” in snailfish living in the hadal zone. Our findings provide further insights into symbiotic associations in the hadal biosphere.